"When I finally heard my own voice": Dialogical Articulations of Self-making When Moving out of Islam in the Netherlands - Vliek, Maria (Journal of Muslims in Europe, 2019)
The purpose of this article is to expand on Dialogical Self Theory and to illustrate its benefits for the analysis of narratives of leaving Islam in a post-migration context. With leaving one's religion, complex mechanisms of doubt, uncertainty, and ethical self-making come to the fore. Being in a post-migration context raises additional issues of intersectionality. Dialogical Self Theory is well-suited for the close-reading and in-depth analysis of such trajectories out of Islam, because it firstly considers the actual voices and their interaction in self-narrative. Secondly, Dialogical Self Theory allows for the recognition of the complex embeddedness of these voices in discursive power-structures. Thirdly, it considers self-making agentic properties. The particular usefulness of this theory will be exemplified by applying its analytical tools to one such trajectory.